2023
DOI: 10.1038/s41467-023-37248-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the CA2-ventral CA1 pathway reverses social discrimination dysfunction in Shank3B knockout mice

Abstract: Mutation or deletion of the SHANK3 gene, which encodes a synaptic scaffolding protein, is linked to autism spectrum disorder and Phelan-McDermid syndrome, conditions associated with social memory impairments. Shank3B knockout mice also exhibit social memory deficits. The CA2 region of the hippocampus integrates numerous inputs and sends a major output to the ventral CA1 (vCA1). Despite finding few differences in excitatory afferents to the CA2 in Shank3B knockout mice, we found that activation of CA2 neurons a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 124 publications
(191 reference statements)
0
6
0
Order By: Relevance
“…These deficits result in impaired social recognition memory (147, 156,158), object location memory (147, 149, 155), and spatial learning and memory (149,152,153,155,156), particularly affecting longterm memory processes. In contrast to the above observations, Peca et al (159) have reported that the frequency and amplitude of miniature excitatory postsynaptic currents and Morris water maze performance in Shank3B mutant mice are comparable to those of controls. Similarly, Cope et al (160) have found impaired social but not object location memory in Shank3B KO mice.…”
Section: Phelan-mcdermid Syndromementioning
confidence: 67%
See 1 more Smart Citation
“…These deficits result in impaired social recognition memory (147, 156,158), object location memory (147, 149, 155), and spatial learning and memory (149,152,153,155,156), particularly affecting longterm memory processes. In contrast to the above observations, Peca et al (159) have reported that the frequency and amplitude of miniature excitatory postsynaptic currents and Morris water maze performance in Shank3B mutant mice are comparable to those of controls. Similarly, Cope et al (160) have found impaired social but not object location memory in Shank3B KO mice.…”
Section: Phelan-mcdermid Syndromementioning
confidence: 67%
“…Similarly, Cope et al. ( 160 ) have found impaired social but not object location memory in Shank3 B KO mice. Contradictory findings across these studies may be attributed to mutations of various Shank3 isoforms.…”
Section: Abnormalities In the Structure And Function Of The Hippocamp...mentioning
confidence: 79%
“…Further, under baseline conditions Shank3B -/mice demonstrated increased power in the gamma band. Cope et al (Cope et al, 2023) recorded from the ventral CA1 region of the same Shank3B -/mice during social behavior and observed no change in theta or gamma power in the mutants but did observe that chemogenetic activation of the CA2 region increased CA1 theta power specifically in the KO mice and led to a concomitant rescue of social behavioral deficits. Interestingly, a recent study from Tao et al (Tao et al, 2022) conducted a similar study, recording in vCA1 of control and Shank3 -/mice during a social discrimination task and found a decrease in the fraction of cells encoding social information during the task, as well as a decrease in the power of SWRs and a decrease in the correlation between cell sequences observed during behavior and SWRs.…”
Section: Hippocampal Neural Circuit Activity In Asd Model Micementioning
confidence: 85%
“…The novelty T-maze focuses on both spatial learning and memory, and with its short, 1minute inter-trial interval, this procedure is examining spatial working memory (Sharma et al, 2010;d'Isa et al, 2021). The 3-chamber social interaction test is assessing baseline sociability and also social recognition memory (Meira et al, 2018;Tzakis and Holahan, 2019;Wang and Zhan, 2022;Cope et al, 2023;Wei et al, 2024). Finally, the Barnes maze tests both spatial learning and working memory in intra-day trials, while simultaneously testing long-term contextual and spatial memory in inter-day trials and the probe test (Bach et al, 1995;Sharma et al, 2010;Rosenfeld and Ferguson, 2014;Pitts, 2018).…”
Section: Prosapip1 Is Required For Learning and Memorymentioning
confidence: 99%